THE ROLE OF TIME IN POST-MERGER INTEGRATION - Marina Apaydin (European Scientific Journal, ESJ, 2014)
This paper investigates the dual role of time in post-merger integration (PMI). Prior research has focused on the determinants of M&A success, and highlighted the importance of meeting implementation schedules as a pivotal, yet usually unachieved, goal of a PMI. In this paper, I propose a dual explanation of this phenomenon: the implementation schedule timelines are usually too optimistic, and actual implementation is too slow. The theorizing behind these explanations is grounded in the heuristics, biases and temporal orientation literature as well as in Crossan et al.’s (1999) 4I organizational learning framework, which is used to propose how integration complexity influences integration time. Overall, this paper contributes to the explanation of the so-called M&A success paradox (double digit M&A growth in spite of 60%-90% failure rates). Financial analysts, who rarely participate in PMI, underestimate implementation time, which then becomes an excessively aggressive deadline, usually missed because of unanticipated integration complexity.